Hubungan Antara Masa Kerja dan Kelelahan Dengan Stres Kerja Pada Pekerja Konstruksi - Habiba Kamila Fatin; Rini Handayani; Ahmad Irfandi; Putri Handayani (Lembaga Pengembangan Kinerja Dosen, 2023)
The results of a preliminary study conducted by researchers using the DASS 21 questionnaire and stress impact questionnaire on 10 workers at PT Nindya Citra Kharisma KSO's Manggarai